2022
DOI: 10.31235/osf.io/mkzcv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudes towards filial responsibility between 2001 and 2017 in Europe

Abstract: This study examines how attitudes towards filial responsibility (AFR) have changed in 11 European countries between 2001 and 2017, based on data from the International Social Survey Programme. The countries represent different types of welfare states and family traditions. The study also analysed the interconnectedness of age and gender. Results show that in 2017 people felt less filial responsibility than in 2001 in 10 countries. Only in Great Britain did the AFR show a positive change. Negative changes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Despite evidence that attitudes toward filial obligations may have weakened in Western countries (Kääriäinen, et al, 2022), several surveys have shown that most people still believe that adult children should take care of their older parents (Gans & Silverstein, 2006;Herlofson et al, 2011). However, attitudes toward filial obligations vary between countriesfor example, in relation to respondents' age, gender, and labor market status (e.g., Lowenstein & Daatland, 2006: Daatland & Herlofson, 2003Dykstra, 2010;Herlofson et al, 2011).…”
Section: Filial Responsibilitymentioning
confidence: 99%
“…Despite evidence that attitudes toward filial obligations may have weakened in Western countries (Kääriäinen, et al, 2022), several surveys have shown that most people still believe that adult children should take care of their older parents (Gans & Silverstein, 2006;Herlofson et al, 2011). However, attitudes toward filial obligations vary between countriesfor example, in relation to respondents' age, gender, and labor market status (e.g., Lowenstein & Daatland, 2006: Daatland & Herlofson, 2003Dykstra, 2010;Herlofson et al, 2011).…”
Section: Filial Responsibilitymentioning
confidence: 99%